A 10 year asthma programme in Finland: major change for the better. Issue 8 (28th July 2006) - Haahtela, T; Tuomisto, L E; Pietinalho, A; Klaukka, T; Erhola, M; Kaila, M; Nieminen, M M; Kontula, E; Laitinen, L A
Abstract : Background: A National Asthma Programme was undertaken in Finland from 1994 to 2004 to improve asthma care and prevent an increase in costs. The main goal was to lessen the burden of asthma to individuals and society. Methods: The action programme focused on implementation of new knowledge, especially for primary care. The main premise underpinning the campaign was that asthma is an inflammatory disease and requires anti-inflammatory treatment from the outset. The key for implementation was an effective network of asthma-responsible professionals and development of a post hoc evaluation strategy. In 1997 Finnish pharmacies were included in the Pharmacy Programme and in 2002 a Childhood Asthma mini-Programme was launched. Results: The incidence of asthma is still increasing, but the burden of asthma has decreased considerably. The number of hospital days has fallen by 54% from 110 000 in 1993 to 51 000 in 2003, 69% in relation to the number of asthmatics (n = 135 363 and 207 757, respectively), with the trend still downwards. In 1993, 7212 patients of working age (9% of 80 133 asthmatics) received a disability pension from the Social Insurance Institution compared with 1741 in 2003 (1.5% of 116 067 asthmatics). The absolute decrease was 76%, and 83% in relation to the number of asthmatics. The increase in the cost of asthma (compensation for disability, drugs, hospital care, and outpatient doctor visits) ended: in 1993 the costs were €218 million which had fallen to €213.5 million in 2003. Costs per patient per year have decreased 36% (from €1611 to €1031). Conclusion: It is possible to reduce the morbidity of asthma and its impact on individuals as well as on society. Improvements would have taken place without the programme, but not of this magnitude.